Talent in first, second, and third graders: teachers' perspectives vs. educational reality - Diana Castro-Rodríguez; Zulay Pereira-Pérez; Jéssica Solís-Campos; Kenneth Ureña-Rodríguez; Belbeth Villalobos-Obando (Universidad Nacional, Costa Rica, 2010)
The article addresses the subject of talent by emphasizing different conceptions about talent and by proposing an approach to this theme, from the point of view of talent in boys and girls. It also provides an analysis of research conducted with first, second, and third graders in public and private schools of the Costa Rican Education System. Using questionnaires and observations of the dynamics of the classroom as measurement tools, this study contrasts teachers` expectations about their students' talent with the reality of the class environment, pointing out the existing abyss between teachers' beliefs and their professional practices.